The impact of relative CEO compensation on not-for-profit contributions. Issue 2 (20th September 2021) - Kaden, Stacey; Peters, Gary; Sanchez, Juan Manuel; Fleischman, Gary M.
Abstract : Purpose: The authors extend research suggesting that external funders reduce their contributions to not-for-profit (NFP) organizations in response to media-reported CEO compensation levels. Design/methodology/approach: Employing a maximum archival sample of 44, 807 observations from US Form 990s, the authors comprehensively assess the extent that high relative NFP CEO compensation is associated with decreases in future contributions. Findings: The authors find that donors and grantors react negatively to high relative CEO compensation but do not react adversely to high absolute executive compensation. Contributors seem to take issue with CEO compensation when they perceive it absorbs a relatively large portion of the organizations' total expenses, which may hinder the NFP's mission. Additional findings suggest that excess cash held by the NFP significantly exacerbates the negative baseline relationship between future contributions and high relative CEO compensation. Finally, both individual donors and professional grantors are sensitive to cash NFP CEO compensation levels, but grantors are more sensitive to CEO noncash compensation. Research limitations/implications: The authors' data are focused on larger NFP organizations, so this limits the generalizability of the study. Furthermore, survivorship bias potentially influences their time-series investigations because a current year large-scale decrease in funding due to high relative CEO compensation may cause some NFP firms to drop out of the sample the following year due to significant funding reductions. Originality/value: The study makes three noteworthy contributions to the literature. First, the study documents that the negative association between high relative CEO compensation levels and future donor and grantor contributions is much more widespread than previous literature suggested. Second, the authors document that high relative CEO compensation levels that trigger reductions in future contributions are significantly exacerbated by excess cash held by the NFP. Finally, the authors find that more sophisticated grantors are more sensitive to noncash CEO compensation levels as compared with donors.